2018
DOI: 10.1103/physreva.97.033827
|View full text |Cite
|
Sign up to set email alerts
|

Classical imaging with undetected light

Abstract: We obtained the phase and intensity images of an object by detecting classical light which never interacted with it. With a double passage of a pump and a signal laser beams through a nonlinear crystal, we observe interference between the two idler beams produced by stimulated parametric down conversion. The object is placed in the amplified signal beam after its first passage through the crystal, and the image is observed in the interference of the generated idler beams. High contrast images can be obtained e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…Therefore, the paths are indistinguishable and the photons interfere. On the other hand, also classical interpretations exist to explain the effect (16)(17)(18). The quantum mechanical interpretations (3,5,15) were tailored to SPDC processes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the paths are indistinguishable and the photons interfere. On the other hand, also classical interpretations exist to explain the effect (16)(17)(18). The quantum mechanical interpretations (3,5,15) were tailored to SPDC processes.…”
Section: Discussionmentioning
confidence: 99%
“…With this demonstration, a new hyperspectral IR microscopy will be unlocked for practical applications in bioimaging and material analysis. We should also mention the possibility of implementing the method in high gain (43) or stimulated (44,45) regimes of PDC, which is an exciting topic for further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Related measuring techniques allow observation (imaging) at wavelength ranges different from those of the absorption of targeted objects ("imaging with undetected photons" [1,4], referred to as "UP-imaging" in the following) offering serious advantages, e.g., in infrared imaging important in medical, industrial or forensic applications (e.g., cancer diagnostics) [6]. Although recent works have shown that imaging with undetected photons is possible also by "classical" light [7], [8], original works utilizing quantum mechanical principles remained in the focus of interest [9], [10]. These methods are based on the generation of nondegenerate, correlated (entangled) photon pairs of different wavelengths in nonlinear media, by the method of optical parametric down-conversion.…”
Section: Introductionmentioning
confidence: 99%